The Presidency of the United States : a Student Companion. - Pious, Richard M. (Oxford University Press, Incorporated, 2010)
The Presidency of the United States is an illustrated A-to-Z guide to the U.S. Presidency, including biographical sketches of each President and Vice President, along with articles on presidential powers, presidential history, theories about the presidency, presidential elections, advisors and agencies, and information about the daily workings of the White House. The second edition is completely revised up to March 2001, with new Biographies of George W. Bush and Dick Cheney, and completely updated biographies of Bill Clinton and Al Gore.